Forensic electrochemistry: indirect electrochemical sensing of the components of the new psychoactive substance "Synthacaine"1. Issue 16 (21st August 2015) - Cumba, Loanda R.; Kolliopoulos, Athanasios V.; Smith, Jamie P.; Thompson, Paul D.; Evans, Peter R.; Sutcliffe, Oliver B.; do Carmo, Devaney R.; Banks, Craig E.
<x xml:space="preserve">Abstract</x> For the first time a novel indirect, independently validated, electrochemical protocol for the sensing of MPA and 2-AI ("Synthacaine") is reported.